The earth's magnetic interior - Petrovský, Eduard; Ivers, David; Harinarayana, T.; Herrero-Berve, Emilio; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This volume combines review and solicited contributions, related to scientific studies of Division I of IAGA presented recently at its Scientific Assembly in Sopron in 2009. The book is aimed at intermediate to advanced readers dealing with the Earth's magnetic field generation, its historical records in rocks and geological formations - including links to geodynamics and magnetic dating, with magnetic carriers in earth materials, electromagnetic induction and conductivity studies of the Earth interior with environmental applications of rock magnetism and electromagnetism.
11 Rock Magnetic Characterization Through an Intact Sequence of Oceanic Crust, IODP Hole 1256D 11.1 Introduction 11.2 Importance of the Rock Magnetic Characterization 11.3 Background of IODP Site 1256 11.4 Rock-Magnetic Methods 11.5 Results 11.5.1 Hysteresis Results: Coercivity, Saturation Magnetization, and Grain Sizes 11.5.2 Determination of Curie Temperatures 11.6 Observations, Interpretation and Discussion 11.6.1 Curie Temperature as Function of Lithology and Depth 11.6.2 Discussion References
Electronic reproduction
Keywords: Geomagnetism; Earth (Planet) -- Internal structure